LAYANAN KONSELING INDIVIDU DALAM MENGATASI CONDUCT DISORDER PADA REMAJA (STUDI KASUS PADA KLIEN “H”) - Fajar Romadhon (EDUCATIONAL JOURNAL : General and Specific Research, 2023)
Conduct disorder can make individuals like to intimidate others, like to fight, use weapons, destroy their own and other people's belongings, like to run away from home, skip school, steal and commit physical violence to other people or animals. In this study, the researcher aims to find out the description of conduct disorder in client "H" in the Al-Fatah Kenten Mosque complex, Palembang before and after the implementation of individual counseling services, as well as to find out what factors cause client "H" to experience conduct disorder and to implement individual counseling services with cognitive behavioral therapy techniques in overcoming conduct disorder in client "H". In this study, researchers used a qualitative approach, a qualitative approach is research that is intended to understand the phenomenon of what the subject is experiencing, by describing it in the form of words and language in a special natural context by utilizing various natural methods. The subject in this study is the client "H". Based on the results of the study, client "H" who initially experienced conduct disorder, namely likes to intimidate others, likes to fight, uses weapons, destroys personal and other people's belongings, likes to run away from home, skip school, steal and commit violence After conducting research and implementing CBT technical counseling services, thank God, there have been changes, namely not intimidating other people, not fighting, not carrying or using weapons, not damaging your own and other people's belongings, not running away from home, not skipping school, not stealing and not physically abusing other people or animals. In addition, individual counseling services using the CBT technique are a form of application given to client "H", namely by carrying out a process of therapy or healing from negative behavior and thoughts to change them into positive behaviors and thoughts, so that clients can think individually and can carry out positive actions or behaviors according to the direction of the counselor.